2022
DOI: 10.1111/andr.13197
|View full text |Cite
|
Sign up to set email alerts
|

Low‐intensity extracorporeal shockwave therapy for diabetic men with erectile dysfunction: A systematic scoping review

Abstract: Background: Erectile dysfunction (ED) is a very common complication in men with diabetes mellitus (DM). Low-intensity extracorporeal shockwave therapy (Li-ESWT) offers a promising nonsurgical treatment option for ED. A systematic scoping review investigating the outcomes of Li-ESWT in diabetic men with ED has not yet been performed. Objectives: To systematically review animal and clinical studies related to the use of Li-ESWT for treatment of DM-related ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…In addition, in a systematic review of the literature in the comparisons of LiESWT and PDE5Is versus PDE5Is alone for post‐prostatectomy ED patients, some studies supported a statistically significant improvement in EF with LiESWT and PDE5Is, although several limitations such as small sample sizes, high risk of bias, and high heterogeneity among the studies existed 15 . Furthermore, it was reported that LiESWT may be an effective targeted treatment modality for patients with diabetes 16 . Thus, LiESWT may have the potential to cure not only vasculogenic ED but also neurogenic ED.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in a systematic review of the literature in the comparisons of LiESWT and PDE5Is versus PDE5Is alone for post‐prostatectomy ED patients, some studies supported a statistically significant improvement in EF with LiESWT and PDE5Is, although several limitations such as small sample sizes, high risk of bias, and high heterogeneity among the studies existed 15 . Furthermore, it was reported that LiESWT may be an effective targeted treatment modality for patients with diabetes 16 . Thus, LiESWT may have the potential to cure not only vasculogenic ED but also neurogenic ED.…”
Section: Discussionmentioning
confidence: 99%
“…systematically reviewed animal and clinical studies related to the use of Li‐ESWT for treatment of DM‐related ED 11 . Here, Li‐ESWT is confirmed to be a safe and effective treatment in men with well‐controlled DM and ED 11 …”
Section: Diabetic Metabolic Dysregulation and Sexual Functionmentioning
confidence: 97%
“…The mechanism of Li-ESWT treatment for ED is still unknown. Its effects could be caused by the induction of mechanical stress, which could result in neovescularization, the recruitment of stem cells and growth factors, an improvement in blood flow, and nerve regeneration ( Gruenwald et al, 2013 ; Mason et al, 2022 ). Some studies have shown that Li- ESWT can promote the expression of neuronal nitric oxide synthase (nNOS) in endothelial cells, smooth muscle cells, and nerve cells ( Yao et al, 2022 ).…”
Section: Physical Therapy Of Edmentioning
confidence: 99%